Teacher’s strategies for stimulating EFL students’ active learning in an Indonesian senior high school - Nikmatus Solikhah; Muhammad Jauhari Sofi (English Language Education Study Program, Faculty of Education and Teacher Training, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, Indonesia, 2023)
Organizing effective active learning poses a significant challenge for teachers. The responsibility not only lies in guiding learning activities but also in fostering students' active engagement in the learning process. This study aims to investigate the strategies employed by a female English teacher at a senior high school in Pekalongan, Indonesia to promote active participation among EFL (English as a Foreign Language) students and the challenges she faces. Employing qualitative research with data collected from interviews and observations, various strategies were identified to enhance active learning among EFL students. The study revealed ten effective strategies implemented by the teacher at the school to stimulate active learning, namely encompassing visual-based instruction, problem-solving methods, computer-based instruction, cooperative learning, drama techniques, role-playing, games, peer teaching, Jigsaw learning, and panel discussions. Additionally, the research identified three key challenges faced by the teacher in fostering active learning among EFL students, namely time constraints, preparation limitations, and varying levels of student enthusiasm. In general, this study provides valuable insights that can assist English teachers in selecting suitable active learning strategies tailored to the unique needs of their students and classrooms.